(untitled) (Medical Forum Monthly, 2023)
Objective: The purpose of the present study was to determine the prevalence of different morbidly adherent placenta in previous scar. Study Design: A retrospective cohort study Place and Duration of Study: This study was conducted at the Labour Room of Obstetrics & Gynecology Department at Lady Reading Hospital, Peshawar from January 2022 to December 2022. Materials and Methods: All the singleton pregnancy with gestational age >26 weeks, previous history of caesarean sections, myomectomy, hystrotomy, and placenta previa were included. Types of morbidly adherent placenta, period of gestation, age, duration of scarred uterus, frequency of previous scars, parity, total blood loss, complications, and types of procedure done were recorded for each individual. SPSS version 27 was used for data analysis. Results: The overall mean age 28.62±5.72years. Out of 231 patients, the incidence of morbidly adherent placenta (MAP) was 12.1% (n=28). Of the 28 cases of MAP, the incidence of Placenta accreta, placenta increta, and placenta percreta 15 (6.5%), 7 (3%), and 6 (2.6%) respectively. Age-wise distribution of patients were as follows: 2 (0.9%) in 20-25 years, 19 (8.2%) in30-35 years, and 7 (3%) 35-40 years. Among total MAP cases, the incidence of single, double, thrice, and fourth cesarean section was 4 (1.7%), 6 (2.6%), 8 (3.5%),and 10 (4.3%) respectively. Majority of the females 5.6% (n=13) had parity 4followed by parity 3 in 3.5% (n=8), parity 2 in 1.7% (n=4), and parity 5 in 1.3% (n=3) cases. The number of cases with blood loss >2000 ml and >3000 ml were 10 (4.3%) and 18 (7.8%) respectively. About 21 (9.1%) patients were shifted to ICU. Massive blood transfusion>10 units of packed cells were major complications found in 17 (7.4%) cases followed by bladder injury 13 (5.6%), DISC 6 (2.6%), reopening 6 (2.6%), and acute renal injury in 4 (1.7%). Conclusion: The present study reported that the frequency of morbidly adherent placenta was 12.1% in females with previous scars. MAP is a very rare condition having ten times more frequency in females who had prior history of scar. Placenta accreta was the most prevalent type of MAP due to shorter duration and prior scarred uterus.